2008
DOI: 10.1007/s10397-008-0445-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcervical intrauterine bupivacaine for the management of postoperative pain following endometrial balloon ablation—a pre-trial toxicity study

Abstract: The success of second-generation endometrial ablation performed as day case or outpatient procedure is often hampered by severe postoperative pain. We administered dilute bupivacaine solution into the uterine cavity soon after balloon ablation in ten consecutive women, looking at the safety profile of bupivacaine. Three hours postoperative serum bupivacaine levels were well below the toxic level in all women with no side effects reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It is likely that the speculum insertion measurement is a surrogate for a patient's overall tolerance of pain and/or anxiety. Pain with speculum insertion occurs in many conditions such as dyspareunia, vulvar vestibular syndrome, and vaginismus (21,22). To control for possible confounding as the result of a nonequal distribution of women with insertional pain, we excluded those subjects who experienced pain from speculum insertion.…”
Section: Endometrial Biopsy Resultsmentioning
confidence: 99%
“…It is likely that the speculum insertion measurement is a surrogate for a patient's overall tolerance of pain and/or anxiety. Pain with speculum insertion occurs in many conditions such as dyspareunia, vulvar vestibular syndrome, and vaginismus (21,22). To control for possible confounding as the result of a nonequal distribution of women with insertional pain, we excluded those subjects who experienced pain from speculum insertion.…”
Section: Endometrial Biopsy Resultsmentioning
confidence: 99%
“…According to our MEDLINE search, the present study was the first to evaluate efficacy of intrauterine topical levobupivacaine instillation for endometrial biopsy. We could find only one study (22) investigating the application of transcervical intrauterine bupivacaine for the management of postoperative pain following endometrial balloon ablation. They used dilute bupivacaine solution for prevention of severe postoperative pain after balloon ablation in 10 consecutive women; it was found to be effective with no side effects (22).…”
Section: Discussionmentioning
confidence: 99%
“…Bhatia et al ., a pilot study found the intrauterine instillation of dilute bupivacaine (125 mg) was safe, feasible, and effective for PO pain relief after endometrial balloon ablation procedure. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%